Basal serum cortisol and testosterone/cortisol ratio are related to rate of Na+ lost during exercise in elite soccer players - Castro-Sepulveda, M.; Cancino, J.; Fernández-Verdejo, R.; Pérez-Luco, C.; Jannas-Vela, S.; Ramirez-Campillo, R.; Del Coso, J.; Zbinden-Foncea, H. (International Journal of Sport Nutrition and Exercise Metabolism, 2019)
During exercise, the human body maintains optimal body temperature through thermoregulatory sweating, which implies the loss of water, sodium (Na+), and other electrolytes. Sweat rate and sweat Na+ concentration show high interindividual variability, even in individuals exercising under similar conditions. Testosterone and cortisol may regulate sweat Na+ loss by modifying the expression/activity of the cystic fibrosis transmembrane conductance regulator. This has not been tested. As a first approximation, the authors aimed to determine whether basal serum concentrations of testosterone or cortisol, or the testosterone/cortisol ratio relate to sweat Na+ loss during exercise. A total of 22 male elite soccer players participated in the study. Testosterone and cortisol were measured in blood samples before exercise (basal). Sweat samples were collected during a training session, and sweat Na+ concentration was determined. The basal serum concentrations of testosterone and cortisol and their ratio were (mean [SD]) 13.6 (3.3) pg/ml, 228.9 (41.4) ng/ml, and 0.06 (0.02), respectively. During exercise, the rate of Na+ loss was related to cortisol (r = .43; p < .05) and to the testosterone/cortisol ratio (r = -.46; p < .01), independently of the sweating rate. The results suggest that cortisol and the testosterone/cortisol ratio may influence Na+ loss during exercise. It is unknown whether this regulation depends on the cystic fibrosis transmembrane conductance regulator.